Efektivitas Multimedia Interaktif Dalam Meningkatkan Kemampuan Bahasa Anak Usia 4-5 Tahun - Elena Himma Nizrina; Isti Rusdiyani; Fadlullah Fadlullah (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2022)
One of the factors that support the process of renewal and novelty is technology and information, especially utilization and novelty in the field of education. In the process, many learning activities in schools still use direct instructional (conventional) methods and media in the delivery of material for developing children's language skills, one of which is. Annizhomiyyah Kindergarten at Pandeglang Banten is the focus of this research. Aims to determine the effectiveness of using interactive multimedia in improving language skills of children aged 4-5 years. Using an experimental quantitative approach with a one group pre-test post-test design for a sample of 16 children. Data were collected through questionnaires and documentation. The initial results of the pre-test resulted in an achievement rate of 54% and after treatment the post-test results obtained an achievement rate of 95%. This concluded that the use of interactive multimedia in the process can significantly improve the language skills of children aged 4-5 years and based on the existing rating scale. on the criteria of a high level of effectiveness.